Identification of new sources of resistance for pearl millet downy mildew disease under field conditions. Issue 4 (22nd February 2018) - Kanfany, Ghislain; Fofana, Amadou; Tongoona, Pangirayi; Danquah, Agyemang; Offei, Samuel; Danquah, Eric; Cisse, Ndiaga
Abstract: Pearl millet is an important cereal crop for smallholder farmers' food security in Africa and India. However, its production has stagnated due to several factors such as downy mildew (DM). Thus, a study was conducted to identify new sources of resistance from pearl millet inbred lines derived from a collection of landraces originated from West and Central African countries. A set of 101 lines, including 99 inbred lines from West and Central Africa along with a 7042S and SOSAT C 88 as susceptible and resistant checks, respectively, were evaluated under field conditions with infector rows in Bambey and Nioro research stations during the rainy season of 2016. Data on DM incidence and severity, plant height, flowering time, panicle length and productive tillers were recorded. The results showed highly significant differences among lines for all observed traits. Among the tested lines, 55 including SOSAT C 88 were resistant, 16 moderately resistant and 30 including 7042S were susceptible to the disease. Out of the 55 resistant lines, 20 were disease free. Hierarchical ascendant cluster analysis grouped the lines into three clusters with the DM parameters and plant height as the most discriminant factors. Cluster II contains the susceptible lines, while cluster III comprises the moderately resistant lines. The lines which belongs to cluster I were characterized by their resistance to the disease. Further use of these available new sources of resistance will be very useful for improvement of pearl millet for DM resistance and other agronomic traits.